The Uncommon Volunteer - Mills, Chris (Wildlife Rehabilitation Bulletin, 2008)
The purpose of this article is to stimulate thinking, constructive communication, and to advocate on behalf of all wildlife rehabilitation volunteers, with special emphasis on the Uncommon Volunteer.